Use of waste derived fuels in cement industry: a review. Issue 2 (14th March 2016) - Chatziaras, Nickolaos; Psomopoulos, Constantinos S.; Themelis, Nickolas J.
Abstract : Purpose: – Cement production has advanced greatly in the last few decades. The traditional fuels used in traditional kilns include coal, oil, petroleum coke, and natural gas. Energy costs and environmental concerns have encouraged cement companies worldwide to evaluate to what extent conventional fuels can be replaced by waste materials, such as waste oils, mixtures of non-recycled plastics and paper, used tires, biomass wastes, and even wastewater sludge. The paper aims to discuss these issues. Design/methodology/approach: – The work is based on literature review. Findings: – The clinker firing process is well suited for various alternative fuels (AF); the goal is to optimize process control and alternative fuel consumption while maintaining clinker product quality. The potential is enormous since the global cement industry produces about 3.5 billion tons that consume nearly 350 million tons of coal-equivalent fossil and AF. This study has shown that several cement plants have replaced part of the fossil fuel used by AF, such waste recovered fuels. Many years of industrial experience have shown that the use of wastes as AF by cement plants is both ecologically and economically justified. Originality/value: – The substitution of fossil fuels by AF in the production of cement clinker is of great importance both for cement producers and for society because it conserves fossil fuel reserves and, in the case of biogenic wastes, reduces greenhouse gas emissions. In addition, the use of AF can help to reduce the costs of cement production.